Mothers' Challenges after Infants' Discharge from Neonatal Intensive Care Unit: A Qualitative Study - Zeinab Hemati; Mahboobeh Namnabati; Fariba Taleghani; Alireza Sadeghnia (Mashhad University of Medical Sciences, 2017)
ABSTRACTBackground: Mothers with premature infants face certain challenges such as uncertainty on how to deal with their infant's condition and care for it after discharge from neonatal intensive care unit (NICU).Methods: A qualitative design was used to explain mothers' challenges after their infant's discharge from NICUs in Isfahan, Iran, 2015. Purposive sampling was adopted to interview the mothers who could provide us information about the challenges after their infant's discharge. Data collection was performed by interviewing mothers. Data saturation was reached after conducting 23 in-depth, semi-structured interviews. All the data was analyzed by qualitative content analysis.Results: Four themes and nine categories were identified. The themes were incompetence in breastfeeding, dependence on hospital and nurses, feeding tube as a reason for stress, and constantly worried mothers.Conclusion: Mothers have difficulty in meeting their infants' basic needs after discharge. Supporting these mothers can enable them promote their infant's health.